Dietary Eggshell Membrane Powder Improves Survival Rate and Ameliorates Gut Dysbiosis in Interleukin-10 Knockout Mice - Yang, Yongshou; Jia, Huijuan; Lyu, Weida; Furukawa, Kyohei; Li, Xuguang; Hasebe, Yukio; Kato, Hisanori (Frontiers in Nutrition, 2022)
Inflammatory bowel disease (IBD) is known to be associated with compositional and metabolic changes in the gut microbiota. The aim of this study was to investigate whether dietary eggshell membrane (ESM) improves survival rate or ameliorates gut dysbiosis in a spontaneous IBD model of interleukin-10 knockout (IL10−/−) mice. Female C57BL/6J wild-type (WT) and IL10−/− mice (KO) were fed an AIN-93G basal diet or an ESM diet (KOE) for 19 weeks. Gut microbiota profiles were analyzed via 16S rRNA sequencing, and short-chain fatty acids in cecal content were analyzed with high-performance liquid chromatography. The results demonstrated that ESM supplementation significantly improved the survival rate and body composition in KO mice. Alpha diversity analysis of the microbiota revealed that ESM supplementation significantly increased gut microbial diversity, which was decreased in IL10−/− mice. The Firmicutes/Bacteroidetes ratio was recovered to a normal level by ESM supplementation, suggesting that ESM helps maintain the compositional balance of the gut microbiota. ESM increased relative abundance of commensal bacterial Ruminococcus and Bacteroidales S24-7 and reduced the abundance of the proinflammatory-related bacterium, Enterobacteriaceae. Additionally, ESM supplementation promoted the production of butyrate in cecal contents and downregulated the expression of proinflammatory genes, including interleukin-1β (Il-1β) and tumor necrosis factor-α (Tnf-α) in IL10−/− mice colon, indicating anti-inflammatory functions. These findings suggest that ESM may be used as a beneficial dietary intervention for IBD.